The Emergence of Retailing of Generic Medicines: An Awareness Study at Kakinada, Andhra Pradesh - Burlakanti, Kuberudu; Srinivas, Romala Vijaya (Indian Journal of Marketing, 2013)
Using lower price generic medicines for chronic diseases provides efficacy similar to branded medicines. However, previous studies showed that disadvantaged people, who may particularly benefit from cost savings, have low trust on generics and showed increased reluctance to switch to generics. The rural areas include areas of high poverty and minority communities whose members are at high risk for poor health outcomes. However, whether such beliefs exist in these communities has not been reported. We sought to obtain qualitative insights about awareness and usage of generic medication among the people in urban and rural areas of Kakinada city. This survey showed that there is a gap in consumers' awareness and availability of generic medicines in urban and rural areas of Kakinada. The findings of the study suggest that awareness needs to be spread among the customers about generic medicines. Besides, it is an emerging business opportunity for local medical retailers.